ABALONE POACHING: A PHILOSOPHICAL APPROACH (The Pretoria Student Law Review, 2021)
The question that I raise is whether one’s judgment, in other words, knowing the difference between right and wrong, can be clouded by monetary rewards, especially with regard to criminal activity. I take a philosophical approach with specific focus on the environmental concern of abalone poaching. I draw parallels and theoretical answers from Karl E Klare’s ‘Legal culture and transformative constitutionalism’, James Boyd White’s ‘Justice in tension: an expression of law and the legal mind’, John Dugard’s ‘The judicial process, positivism and civil liberty’ and the theories of judgment of Hannah Arendt. Environmental crime is a rising epidemic, especially in South Africa. I argue that not enough attention is paid to such crimes. Sensational crimes seem to have an increased popularity in the press and environmental crimes seem to go deprioritised. There appears to be very few viable solutions for crimes that yield great economic returns. In the mind of the offender, the motivation of great economic returns can be said to override the sense of morality or judgment.
Keywords: judgment; monetary rewards; abalone poaching; Karl E Klare; transformative constitutionalism; Environmental crime